Analysis of Grade 7 Russian Literature Textbooks’ Tasks for Active - productive Reading of Epic Prose (Journal of Educational Sciences, 2026)
The article examines approaches to developing reading competence among 7th-grade students in Russian-language literature classes through a systematic analysis of textbook tasks. It argues for a shift from reproductive engagement with text to meaningful and productive comprehension supported by staged instruction. Drawing on the fourth unit of two state-approved literature textbooks (V. V. Savelieva; N. P. Loktionova), the study identifies task types calibrated to different levels of textual understanding and their distribution across lessons. On this empirical basis, it proposes a five-stage methodological model for forming reading competence: motivational-orientational; semantic (close) reading; analytical-interpretative; reflective-productive; and evaluative-generalizing. The emphasis stated in the title of the article reflects its dual focus: an analysis of Grade 7 Russian literature textbook tasks on epic prose and the design of a five-stage model of active-productive reading. The paper demonstrates that this model is directly derived from the empirical analysis of tasks and is designed to supplement and extend the existing task spectrum by systematically targeting meaningoriented and interpretative levels of comprehension. Classroom-oriented readings of short stories by V. Nabokov and V. Tendryakov illustrate how the model operationalizes transitions from surface comprehension to deeper inference, interpretation, and value judgment. A mixed-methods study was used. Teachers from School-Gymnasium No. 209 in Almaty participated in the survey. The results are intended for literature teachers, methodologists, and curriculum designers and can inform lesson planning, assessment design, literature clubs, and teachertraining seminars. The study contributes a replicable framework for aligning textbook tasks with progressive levels of comprehension and for integrating semantic reading practices into the middle-school literature curriculum. Keywords: reading competence, semantic reading, productive reading, literary text analysis, methodological model, Grade 7 curriculum, epic prose.